Researching the Implementation of Work-based Learning within Higher Education: Questioning Collusion and Resistance - Fiona Reeve; Jim Gllacher (Adult Education Research Conference, 2000)
This paper develops a framework for characterising the range of work-based learning practices within higher education. It suggests some directions for research in the context of competing discourses.